Risk factors affecting the success of percutaneous cholecystostomy treatment in high-risk patients with acute cholecystitis - Aktas, Aydin; Ulusahin, Mehmet; Burak Cekic, Arif; Ates, Muhammet; Enre Reis, Murat; Tayar, Serkan; Arif Usta, Mehmet; Guner, Ali; Turkyilmaz, Serdar; Agaoglu, Nazim; Calik, Adnan (Annals of Medical Research, 2021)
Aim: The aim of study was to examine the results of percutaneous cholecystostomy (PC) in high-risk patients with acute cholecystitis (AC). Material and Methods: In the retrospective study, records of patients with PC were examined. An American Society of Anesthesiologists (ASA) score was used for surgical risk. AC severity was evaluated according to Tokyo guidelines (TG) 18. TG 18 grade III, TG 18 grade II and I high surgical risk patients with AC were included in the study. Risk factors affecting the success of PC were investigated. Results: Seventy patients were included in the study. The median folllow-up time was eight (1-119) months. The clinical success rate of PC and rate of recurrence were 85.7% and 10.0%, respectively. PC catheter-related complications were occurred at four patients. The mortality rate was 14.3%. An ASA ≥ IV score (p=0.005), chronic obstructive pulmonary disease (p=0.04), elevation in total bilirubin (p=0.02), and duration of PC 14 days (p 0.001) were found to be risk factors reducing the success of PC. In the logistic regression analysis, an ASA ≥ IV score (p=0.03) and duration of PC 14 days (p=0.005) were found to be independent risk factors reducing the success of PC. Conclusion: PC can be used safely in high-risk patients with AC. The PC catheter should not be removed in 14 days and surgical treatment should be considered for patients with ASA ≥ IV score.